Catalisadores de CuO, Fe2O3 ou Co3O4 suportados em TiO2, CeO2 ou ZrO2: preparação via Sol-gel in situ ou impregnação e avaliação na redução de NO com CO - Sierra-Pereira, Cristiane Alves (Universidade Federal de São Carlos, 2012)
The minimization of the emissions of nitrogen oxides (NOx) is a subject of crucial interest, since them cause serious environmental problems which affect human health, vegetation and fauna. With the purpose to abate NOx, processes involving their catalytic reduction show strong potential. In the case of the reduction of NO with CO a meaningful advantage arises, once both pollutants are removed simultaneously. In order to obtain efficient and stable catalysts for this reaction, many studies have been done with the aim to improve the catalytic activity by achieving a better favorable metal-support interaction to the occurrence of the reaction and a better distribution of the active phases on the support. In this context, the objective of this study was to prepare Cu, Fe and Co based catalysts supported on TiO2, CeO2 and ZrO2 to be applied in the abatement of NO with CO. The addition of the precursors of the active phases was made during the synthesis of the support via the sol-gel method (in situ addition). Furthermore, catalysts with the same composition were prepared by conventional methods. Results from the N2 adsorption/desorption measurements show that the sol-gel method was efficient to prepare supports with improved textural properties. H2-TPR and UVVIS-DRS data evidenced the presence of Cu, Fe or Co oxides in the respective catalysts, which mostly did not show characteristic X-ray diffraction peaks of those oxide phases, suggesting their high dispersion on the supports. In general, results of the reduction of NO to N2 with CO revealed that the catalysts prepared via sol-gel are as active as those prepared by conventional routes, which demonstrate the great potential of the catalysts preparation via the sol-gel in situ procedure, which diminishes the number of the synthesis steps saving time and energy. In general, among the studied supports, ceria presented a more favorable metal-support interaction. In the presence of O2, SO2 and water steam, catalysts 6,5Cu/CeP, 5,5CuZrSG and 8,4Fe/TiC showed no significant changes in their activity and selectivity, indicating that they present high stability to be used under the severe conditions of real processes.
Keywords: Engenharia química; Abatimento de NO; Redução (Química); Sol-gel - método; Óxidos metálicos; CO; Sol-gel, In situ; CuO; Fe2O3; Co3O4; TiO2; CeO2; ZrO2; Abatement; Reduction; NO; CO; Sol-ge; In situ; CuO; Fe2O3; Co3O4; TiO2; CeO2; ZrO2; ENGENHARIAS::ENGENHARIA QUIMICA